Elongation of protein synthesis: structural basis of the peptide bond - Rodnina, Marina (Henry Stewart Talks, 2007)
The ribosome, Chemistry of peptide bond formation, Structure of the peptidyl transferase center of the ribosome, Structures of the catalytic subunit with reaction substrates and transition state analogs, Induced fit in peptide bond formation and peptidyl-tRNA hydrolysis, Reaction pathways of catalyzed and uncatalyzed reactions, pH dependence of catalysis, Entropic catalysis, Role of active site residues, Importance of 2' OH of A76 of the tRNA in the P site, The mechanism of peptide bond formation